A Psicologia do trabalho e as Clínicas do trabalho no Brasil - José Newton Garcia de Araújo; Vanessa Andrade de Barros (Universidade do Porto, 2019)
This paper presents a brief discussion about Work psychology, in Brazil, and its interfaces with the Work clinics and the Worker's health field. Our starting point is the set of papers presented by Brazilian researchers in the "France-Latin America Symposium". A methodological cut has allowed us to elect these disciplinary fields by reading titles, reviews and paper references. The texts showed a significant convergence between the following themes : social and critical orientation, keeping interest in the working subjects ; the complexity and singularities that lead their work experiences ; the processes of constitution, the psychic and political-social commitments of these workers. We believe that a synthesis of the researches presented in this colloquium reflects the current moment of the Work Psychology in Brazil, in its connections with the Work Clinics and the Worker's Health.